THE FOCUS OF THE SMALL STRUGGLE IN MATCHО AND THE DECISION OF THE SOVIET AUTHORITY IN THIS AREA - Botirjon Makhamadalievich Tojibaev (Journals Park Publishing, 2023)
In this article showed that according to some researches, at this time the tsarist government as Russian Empire gave the province the office of self-government and gave it the status of autonomy and the center of Matcho was at different times the villages of Oburdan and Madrushkat.
Keywords: Oburdan, Matcho, Madrushkat, self-government, soviet authority, struggle.